Improving Students Learning Motivation trough Group Guidance Services - sadif, ria safaria; Samsaifil; Tarno; Wanti Stevania (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of the study was to determine the significance of increasing students' learning motivation through the provision of group guidance services to students of SMAN 3 Baubau. This research used quantitative method, with pre-experimental design using one group pretest-posttest design. This research was conducted at SMAN 3 Baubau with the research subject of class XI students who have low learning motivation category. The population in this study totalled 48 students. Sampling through nonprobability sampling technique with the technique of determining the number of samples through purposive sampling. The number of research samples is 8 students who have low learning motivation. The posttest results consisted of 5 students with a percentage of 62% in the medium category and 3 students with a percentage of 38% in the high category and there were no low category students. In the Ranks Uiji Wilcoxon Signed-Ranks data shows that negative ranks or negative differences between pre-test and posttest results are 0 in the N value, Mean Rank and Sum of Ranks. On positive ranks the results of the pres test posttest show 8 on the n value, mean ranks or an average increase of 4.50 and sum of ranks with a value of 36.00. While the level of similarity in the pretest and post test scores is 0, where the value of 0 is said to be no similarity in the pres test and posttest scores. It can be concluded that group guidance services are effective in increasing students’ learning motivation.